CUDA implementation of fractal image compression - Al Sideiri A.; Alzeidi N.; Al Hammoshi M.; Chauhan M.S.; AlFarsi G. (Springer, 2023)
Encoding (symbols); Fractals; Graphics processing unit; Image coding; Program processors; Signal encoding; Signal to noise ratio; CUDA; Fractal image compression; Fractal image compression algorithm; Graphical processing unit (GPUs); Lossy image compression; Parallel processing; Peak signal to noise ratio; Quad-tree partitioning; Image compression